Set up a system of equations:
![\text{Total shirts bought}](https://tex.z-dn.net/?f=%20%5Ctext%7BTotal%20shirts%20bought%7D%20)
![x + y = 9](https://tex.z-dn.net/?f=%20x%20%2B%20y%20%3D%209%20)
![\text{Total cost}](https://tex.z-dn.net/?f=%20%5Ctext%7BTotal%20cost%7D%20)
![10x + 7y = 72](https://tex.z-dn.net/?f=%2010x%20%2B%207y%20%3D%2072%20)
x represents how many tee shirts were bought, and y represents how many long sleeve shirts were bought.
For the first equation, subtract y from both sides to get x by itself:
![x = 9 - y](https://tex.z-dn.net/?f=%20x%20%3D%209%20-%20y%20)
We'll now use substitution. Since x is equal to a value, we can substitute this value for the other equation:
![10(9-y) + 7y = 72](https://tex.z-dn.net/?f=%2010%289-y%29%20%2B%207y%20%3D%2072%20)
Distribute the 10 to both terms in parentheses:
![10 \times 9 = 90](https://tex.z-dn.net/?f=%2010%20%5Ctimes%209%20%3D%2090%20)
![10 \times -y = -10y](https://tex.z-dn.net/?f=%2010%20%5Ctimes%20-y%20%3D%20-10y%20)
![90 - 10y +7y = 72](https://tex.z-dn.net/?f=%2090%20-%2010y%20%2B7y%20%3D%2072%20)
Combine like terms:
![-10y + 7y = -3y](https://tex.z-dn.net/?f=%20-10y%20%2B%207y%20%3D%20-3y%20)
![90 - 3y = 72](https://tex.z-dn.net/?f=%2090%20-%203y%20%3D%2072%20)
Subtract 90 from both sides:
![-3y = -18](https://tex.z-dn.net/?f=%20-3y%20%3D%20-18%20)
Divide both sides by -3 to get y by itself:
![y = 6](https://tex.z-dn.net/?f=%20y%20%3D%206%20)
6 long sleeve shirts were bought.
Now you have a value for y. Input this value into the first equation:
![x + 6 = 9](https://tex.z-dn.net/?f=%20x%20%2B%206%20%3D%209%20)
Subtract both sides by 6 to get x by itself:
![x = 3](https://tex.z-dn.net/?f=%20x%20%3D%203%20)
3 tee shirts were bought.
The answer is B. 3 tee shirts and 6 long sleeve shirts.